A nuclear factor Y interacting protein of the GRAS family is required for nodule organogenesis, infection thread progression, and lateral root growth - Battaglia, Marina Esther (2014)
A C subunit of the heterotrimeric nuclear factor Y (NF-YC1) was shown to play a key role in nodule organogenesis and bacterialinfection during the nitrogenfixing symbiosis established between common bean (Phaseolus vulgaris) andRhizobium etli.Toidentify other proteins involved in this process, we used the yeast (Saccharomyces cerevisiae) two-hybrid system to screen for NF-YC1-interacting proteins. One of the positive clones encodes a member of the Phytochrome A Signal Transduction1 subfamily ofGRAS (for Gibberellic Acid-Insensitive (GAI), Repressor of GAI, and Scarecrow) transcription factors. The protein, namedScarecrow-like13 Involved in Nodulation (SIN1), localizes both to the nucleus and the cytoplasm, but in transgenicNicotianabenthamianacells, bimolecularfluorescence complementation suggested that the interaction with NF-YC1 takes placepredominantly in the nucleus. SIN1 is expressed in aerial and root tissues, with higher levels in roots and nodules.Posttranscriptional gene silencing ofSIN1using RNA interference (RNAi) showed that the product of this gene is involvedin lateral root elongation. However, root cell organization, density of lateral roots, and the length of root hairs were not affectedbySIN1RNAi. In addition, the expression of the RNAi ofSIN1led to a marked reduction in the number and size of nodulesformed upon inoculation withR. etliand affected the progression of infection threads toward the nodule primordia. ExpressionofNF-YA1and the G2/M transition cell cycle genesCYCLIN BandCell Division Cycle2was reduced inSIN1RNAi roots. Thesedata suggest that SIN1 plays a role in lateral root elongation and the establishment of root symbiosis in common bean.